Implementation Of Least Significant Bit (LSB) Algorithm For Data Security In Digital Imagery - Penda Sudarto Hasugian Hasugian; Agustina Simangunsong (SEAN Institute, 2020)
In this study, a software was built that can insert text messages into image files (steganography) and steganalisis or detect the presence or absence of secret messages in an image. Imagery is the most commonly used medium for inserting secret messages, as it can hide messages very well and is widely available. The built software implements steganalisis with the Least Significant Bit (LSB) algorithm which is the most widely used message insertion algorithm. Steganlysis software is built using LSB algorithms to perform insertion and extract insertion messages on image files. The LSB algorithm in this study used the microsoft Visual Basic 6.0 programming language tools. Based on the software tests conducted, it can be seen that the software can run well on insertion and detect the presence or absence of secret messages on image files.